Tipe Kepribadian Ektrovert-Introvert dan Kecemasan Mahasiswa pada masa Pandemi Covid-19 - Ari Pamungkas (Syams, 2020)
This paper explores the understanding of student personality types during the Covid-19 Pandemic in dealing with changes , such as lecture methods being important to anticipate the emergence of anxiety and find efforts to deal with anxiety that are in accordance with the personality type, in the form of prevention or after an anxiety incident. The method used in this article is descriptive quantitative with samples of 100 students of the Faculty of Ushuluddin Adab and Da'wah , by using purposive random sampling technique. The data in this study used 2 standardized instruments, namely the Eysenck Personality Inventory (EPI) instrument to measure extrovert-introvert personality and anxiety levels using the DASS-21 instrument. The survey results revealed , that the students who have levels of anxiety during the 19th dominant covid pandemic have introverted personality types. This situation shows the introverted personality types ber i siko greater anxiety than students with extrovert personality type.